Home gardens in Nepal - Gotor, Elisabetta; Bioversity International (Bioversity International, 2013)
Home gardens have traditionally played an important role in the production of food, fodder, fuel, medicines, spices, flowers and building materials throughout Nepal. These small areas of land close to the homestead—often incorporated within a larger farming system—harbour high biodiversity, provide a large share of families food consumption and contribute income. Due to their small size, however, home gardens have been overlooked as a way of improving the nutritional diversity and livelihoods of poor rural communities. The ‘Home Garden Project’ in Nepal, set to turn this around. This publication is part of the Bioversity International’s series of Impact Assessment Briefs that aim to inform readers about the major results of evaluations carried out by the centre. The Briefs summarize conclusions and methods of more formal papers published in peer-reviewed journals.